Factors affecting small and medium enterprises access to capital: Evidence from Vietnam - Nguyen, Hong Thu; Nguyen, Thi Le Hang; Dao, Quyet Thang; Nguyen, Ngoc Tien (Nurture, 2024)
Purpose: The capacity of a business to operate and grow depends on its capital, particularly for small and medium-sized businesses (SMEs). However, access to capital sources depends on many factors such as collateral assets, business plans requiring loans, the social relations of business owners, etc. This study identifies factors affecting SMEs’ access to capital in Vietnam. Design/Methodology/Approach: A typical survey was conducted on 450 SMEs in Vietnam, and structural model analysis methods were employed through PLS-SEM software to analyze the data. Findings: Research results show that there are nine groups of factors affecting the ability of SMEs in Vietnam to access capital ranked from high to low level of influence, including (i) operational characteristics of the business, (ii) financial reporting, (iii) financial behaviour of enterprises, (iv) social relations of enterprises, (v) capability of the enterprise, (vi) production and business plan of the enterprise, (vii) ability to adapt to the risks of the enterprise, (viii) characteristics of the business owner and the lowest is institutional environment. Conclusion: Regression analysis proved to be useful in identifying nine groups of elements that impact SMEs’ access to capital in Vietnam. The study has proposed management implications to improve access to capital for SMEs in Vietnam. Research Limitations and Implications: The study selected samples based on the principle of random convenience, so the study’s sample does not represent all SMEs in Vietnam according to the distribution of regions and territories where the businesses are located. Practical Implications: This research has practical significance in supporting managers at SMEs to make decisions to improve access to capital for businesses contributing to sustainable business development. Contribution to the Literature: This research makes a significant contribution to the field of practical research on capital and capital access for SMEs in Vietnam.